In vitro antimalarial activity of Jaloh leaves extract on Plasmodium falciparum - Nuzul Asmilia; Amalia Sutriana; Erdiansyah Rahmi; . Sugito (Syiah Kuala University, 2011)
Malaria still cause health problem in tropics including Indonesia, since its generate high mortality rate. Medication of Malaria has been performed long time ago without optimum result. One reason is the high rate of P.falciparum resistance on conventional antimalaria drug. This research aim to evaluate the activity of jaloh leaves extract (Willow leaves) on the inhibition of P.falciparum in vitro.This was a laboratory experimental research that using Indonesian isolates of cloroquin resistance P.falciparum obtained from NAMRU-2, Jakarta. P.falciparum isolate that has been synchronized were divided in to 3 groups of treatment : Jaloh leaves ethanolic extract, jaloh leaves ethyl acetate extract, and jaloh leaves n-hexane extract. Each group were then alloted into 5 dosage levels: 6,25ug/ml; 12,50ug/ml; 25,00ug/ml; 50,00ug/ml; and 100ug/ml. The observation of parasitemia degree were done 48 hours post-incubation in which the thick blood smear were colored with Giemsa and then examined using bioculer microscope. Data were analyzed using one way ANOVA and Newman-Keuls test. The result showed that the percentage of P.falciparum growth inhibition were sinificantly different (P0.05) among treatments wherein ethanol extract and ethyl acetate extract more inhibit P.falciparum growth than the hexane extract. The administration of different dosage also resulted in significance different (P0.05) of P.falciparum growth inhibition. This research concludes that jaloh leaves extract could inhibit P.falciparum growth.